2019
DOI: 10.1111/let.12288
|View full text |Cite
|
Sign up to set email alerts
|

Permian macroburrows as microhabitats for meiofauna organisms: an ancient behaviour common in extant organisms

Abstract: Meiofaunal organisms are indirectly influenced by the activity of benthic macroinvertebrates within the sediment, which plays a role in modifying physical and chemical characteristics of the habitat. The association of meiofaunal organisms and macroburrows is well known in modern environments, but the record of this relationship in the geological record is still incipient. This study documents diminutive burrows (Helminthoidichnites tenuis) associated with the surface of macroburrows (Palaeophycus tubularis) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 64 publications
0
7
0
Order By: Relevance
“…The organisms responsible for Palaeophycus constitute a eurybathic, facies-crossing ichnogenus, which occurs in a wide range of marine and non-marine settings. Palaeophycus itself represents a combined feeding/temporary dwelling burrow made by organisms with filter-, suspensive- and carnivore-feeding behaviors 20,26 . Their presence suggests high rates of organic matter transport to the sediment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The organisms responsible for Palaeophycus constitute a eurybathic, facies-crossing ichnogenus, which occurs in a wide range of marine and non-marine settings. Palaeophycus itself represents a combined feeding/temporary dwelling burrow made by organisms with filter-, suspensive- and carnivore-feeding behaviors 20,26 . Their presence suggests high rates of organic matter transport to the sediment.…”
Section: Introductionmentioning
confidence: 99%
“…Dense occurrences of Palaeophycus tubularis , and the absence of other macroburrows, have been interpreted as evidence of ecologically stressful conditions during substrate colonization including salinity fluctuations, oxygen depletion, and turbidity. These features can also indicate a change in sedimentation rate or other conditions 26 .…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, recognition of meiofauna burrows in sedimentary rocks is in early development (see also McIlroy, 2022). In the small number of available publications (Knaust, 2007, 2010, 2021; Baliński et al ., 2013; McMenamin, 2016; Parry et al ., 2017; Villegas‐Martin & Netto, 2018; Biddle et al ., 2021), meiofauna burrows may be identified by their constant diameter and straight to sinusoidal character, with a producer being sometimes preserved at the end of the trace (Knaust, 2007, 2021). The traces generally have no ichnotaxonomic names, with only few exceptions that could be assigned to Cochlichnus , Trichichnus , Helminthopsis or Helminthoidichnites (Knaust, 2007; Villegas‐Martin & Netto, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…In the small number of available publications (Knaust, 2007(Knaust, , 2010(Knaust, , 2021Bali nski et al, 2013;McMenamin, 2016;Parry et al, 2017;Villegas-Martin & Netto, 2018;Biddle et al, 2021), meiofauna burrows may be identified by their constant diameter and straight to sinusoidal character, with a producer being sometimes preserved at the end of the trace (Knaust, 2007(Knaust, , 2021. The traces generally have no ichnotaxonomic names, with only few exceptions that could be assigned to Cochlichnus, Trichichnus, Helminthopsis or Helminthoidichnites (Knaust, 2007;Villegas-Martin & Netto, 2018). Features diagnostic of meiofauna tunnels (straight to sinusoidal shape, constant diameter) are seen in published photographs interpreted by some authors as keratose sponges (e.g.…”
Section: Endobenthosmentioning
confidence: 99%
“…Trace fossils of mesohaline and fully marine invertebrate organisms are common in the Rio Bonito (median and upper portions) and Palermo formations (e.g., Buatois et al, 2001a, 2001b, 2007; Gandini et al, 2010; Netto, 1994, 1998; Villegas‐Martín & Netto, 2019). Bioerosion structures have also been recorded in valves from mollusc‐dominated shell beds preserved in the transgressive deposits of the Rio Bonito Formation (Schmidt‐Neto et al, 2018).…”
Section: Geological and Geographical Contextmentioning
confidence: 99%